(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2025)
Robotic systems and the Internet of Robotic Things (IoRT) are rapidly expanding into domains such as healthcare, industry, logistics, and smart environments, bringing significant benefits but also exposing new security challenges. Because robots exchange data, interact with cloud and edge platforms, and operate autonomously, cyber incidents can cause information breaches and physical harm. This scoping review maps current research on IoRT security by analyzing studies published in the last five years. Using PRISMA methodology, the review identifies the main threats affecting IoRT systems-ranging from adversarial manipulation and data leakage to insecure wireless communication and vulnerabilities in learning-based components. The examined literature shows that most solutions focus on protecting data confidentiality, ensuring integrity of robotic behavior, and applying cryptographic or AI-driven defense mechanisms, while protocol-level security remains notably underexplored. Overall, the review reveals a growing yet fragmented field and highlights the need for more systematic evaluation of communication protocols and robust, trustworthy AI methods to secure increasingly autonomous robotic systems.